2016
DOI: 10.3758/s13415-016-0452-1
|View full text |Cite
|
Sign up to set email alerts
|

Error monitoring is related to processing internal affective states

Abstract: Detecting behavioral errors is critical for optimizing performance. Here, we tested whether error monitoring is enhanced in emotional task contexts, and whether this enhancement depends on processing internal affective states. Event-related potentials were recorded in individuals with low and high levels of alexithymia-that is, individuals with difficulties identifying and describing their feelings. We administered a face word Stroop paradigm (Egner, Etkin, Gale, & Hirsch, 2008) in which the task was to classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 73 publications
5
20
0
Order By: Relevance
“…The authors argued that this modulation of the Ne/ ERN might originate in affect-driven changes to dopamine levels in the MFC, possibly in conjunction with an activation of the noradrenergic system due to increased arousal. Furthermore, spatial incompatibility entails response conflict (Simon, 1990) and recent evidence suggests that conflict and errors triggers negative affect (Aarts, De Houwer, & Pourtois, 2012Dreisbach & Fischer, 2012;Maier, Scarpazza, Starita, Filogamo, & Làdavas, 2016;Schouppe et al, 2015;. As a result, conflict elicited by unexpected action effects in our prime task could have generated negative affect, which in turn could have increased the sensitivity of detecting negatively valent errors in the probe task.…”
Section: Discussionmentioning
confidence: 88%
“…The authors argued that this modulation of the Ne/ ERN might originate in affect-driven changes to dopamine levels in the MFC, possibly in conjunction with an activation of the noradrenergic system due to increased arousal. Furthermore, spatial incompatibility entails response conflict (Simon, 1990) and recent evidence suggests that conflict and errors triggers negative affect (Aarts, De Houwer, & Pourtois, 2012Dreisbach & Fischer, 2012;Maier, Scarpazza, Starita, Filogamo, & Làdavas, 2016;Schouppe et al, 2015;. As a result, conflict elicited by unexpected action effects in our prime task could have generated negative affect, which in turn could have increased the sensitivity of detecting negatively valent errors in the probe task.…”
Section: Discussionmentioning
confidence: 88%
“…Theoretically, this is of interest since recent research suggested that conflict and errortriggered affect is not only epiphenomenal, but has a functional role as a driving force for control adjustments (Inzlicht et al, 2015;van Steenbergen, Band, & Hommel, 2009;van Steenbergen, 2015;Dignath et al, in press). This speculation is supported by studies showing that errors (and conflict between responses more generally) lead to negative affective evaluations (Aarts, De Houwer, & Pourtois, 2012;Maier, Scarpazza, Starita, Filogamo, & Làdavas, 2016), trigger avoidance motivation Hochman et al, 2017) and are accompanied by physiological changes which are typical for negative, high arousing affect (Hajcak, McDonald & Simons, 2003;Spruit, Wilderjans, & van Steenbergen, 2018;Hajcak & Foti, 2008).…”
Section: Highlightsmentioning
confidence: 92%
“…Alexithymia reflects individual differences in the ability to detect and describe self-generated emotion (Taylor, Bagby, & Parker, 1999). Recent investigations suggest that increasing alexithymia predicts reduced neural conflict monitoring (i.e., reduced ERN amplitudes; Maier, Scarpazza, Starita, Filogamo, & Làdavas, 2016) and poorer behavioural regulation of conflict (de Gallan, Sellaro, Colzato, & Hommel, 2014). While these results should be confirmed in larger samples, they support the The Emotive Nature of Conflict 21 idea that conflict-driven control relies partially on sensitivity to internally generated affective states.…”
Section: The Emotive Nature Of Conflict and Control Implementationmentioning
confidence: 99%